What does green logistics bring to the circular economy? An exploratory study to connect the dots - de Jesus, Everaildes (2024)
The world population has increased, and consumerist trends have intensified the need for initiatives to minimize industrial activities' environmental and social impacts. Companies and governments are increasingly recognizing the relevance of these initiatives, yet many firms still follow resource extraction models that hinder sustainability efforts. While previous studies have explored the link between green logistics and the circular economy, gaps remain in understanding how these practices can be leveraged to achieve a competitive advantage in different international contexts. This research aims to fill these gaps by exploring the role of green logistics in promoting the circular economy, using a quantitative approach based on Brazilian and Portuguese companies. The study, therefore, focuses on how logistics practices can support the adoption of circular economy initiatives, minimize environmental impacts, and contribute to competitive advantage. The findings from linear regression analysis indicate that green logistics significantly enhances the implementation of circular economy practices, providing both environmental benefits and strategic advantages in the market. This empirical evidence advances the literature by demonstrating that green logistics is not only crucial for circular economy adoption but also for gaining a competitive edge. Our insights are particularly valuable for academia, businesses, and policymakers seeking to promote sustainable practices that are both environmentally responsible and economically viable.